17‐1: Self‐Capacitive Touch Sensor Design for OLED On‐Cell Touch. Issue 1 (28th June 2022) - Tang, Yu-Ying; Lai, Chih-Chung; Lin, Ching-Chun
Abstract : In this work, we propose a self‐capacitive touch sensor for OLED On‐Cell touch. Using self‐capacitive On‐Cell touch sensor, we improve the touch performance including thin cover thickness and large touch area in LGM (Low Ground Mode), miss‐touch issue with multi‐fingers operation and water proof (touch with wet fingers) in traditional mutual‐capacitive OLED On‐Cell touch device. We also reduce the Cs loading of self‐capacitive pattern design in OLED On‐Cell touch structure to get better signal by ratio Δ Cs/Cs. In order to integrate self‐capacitive touch IC and OLED driver IC, we propose a creative OLED TDDI (Touch and Display Driver Integration), which is called NT38770.